Rekomendasi Pembelian Televisi Menggunakan Basis Data Fuzzy Tahani - Abdul Azis; Hindayati Mustafidah (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2012)
By using a standard database, one can handle data that is for sure. But in fact often required the existence of handling the data is sketchy on the system database. Then to resolve the issue can be used the concept of fuzzy logic. This research will implement the concept of fuzzy logic Tahani Model into databases, or commonly called Fuzzy Database Tahani Model. That is, a data base system which can handle data that is fuzzy. The problem will be solved is the process of television recommendation that is most appropriate for users (prospective buyer television). The television recommendation is given on that has fire strength or level of conformity with the criteria of selection of numbers 0 (zero) up to the number 1 (one). The research is expected to help the prospective buyer television in determining which best suits his criteria